The lived experience and caregiver burden of family members supporting chronic stroke survivors - Gian Lisuari Adityasiwi; Nathan Agwin Khenda; Hana Kristina; Ellysa Okky Gusma; Nicholas Adi Perdana Susanto; Fajar Wijanarko (Universitas Udayana dan Diaspora Taipei Medical University, 2026)
Background: Stroke is a debilitating neurological condition and a leading cause of long-term disability worldwide; effective management of chronic stroke survivors requires continuous family support for rehabilitation and recovery. This study aimed to examine the lived experiences and caregiving burden of family members of chronic stroke survivors. Methods: This descriptive qualitative study was conducted in Yogyakarta, Indonesia (March - April 2025), using purposive sampling to recruit eleven primary family caregivers of chronic stroke survivors attending outpatient rehabilitation. Data were collected through semi-structured, face-to-face interviews, audio-recorded, transcribed verbatim, and analyzed using Braun and Clarke’s thematic analysis. Data collection and analysis proceeded concurrently until thematic saturation was reached. Ethical approval and informed consent were obtained. Results: Three themes emerged: health-seeking behavior, access to rehabilitation, and caregiving experiences. Caregivers faced significant physical, psychological, and financial burdens due to continuous care demands, limited access to physiotherapy, and inadequate rehabilitation guidance despite having health insurance. Conclusion: The findings highlight the urgent need for financial support and policy action to advance digital innovation in rehabilitation and reduce the chronic burden caused by systemic gaps.